2018
DOI: 10.1038/s41598-018-29267-z
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Rhythmicity Predicts Synchronization-Continuation Entrainment Performance

Abstract: Rhythmic entrainment—defined as a stable temporal relationship between external periodic signals and endogenous rhythmic processes—allows individuals to coordinate with environmental rhythms. However, the impact of inter-individual differences on entrainment processes as a function of the tempo of external periodic signals remain poorly understood. To better understand the effects of endogenous differences and varying tempos on rhythmic entrainment, 20 young healthy adults participated in a spontaneous motor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 74 publications
3
39
1
Order By: Relevance
“…Some participants 609 even showed inaccurate tapping for rate within the range of their own personal SMT/PPT. This 610 pattern is consistent with another recent study who failed to find a correspondance between 611 SMT and performance on motor syncronization-continuation task (McPherson et al 2018). In 612 that study, synchronization-continuation accuracy was negatively correalted with the overall 613 isochrony of spontaenous tapping, however not to participants' personal SMT rate.…”
Section: Preferred Motor and Perceptual Rhythms 533supporting
confidence: 86%
See 2 more Smart Citations
“…Some participants 609 even showed inaccurate tapping for rate within the range of their own personal SMT/PPT. This 610 pattern is consistent with another recent study who failed to find a correspondance between 611 SMT and performance on motor syncronization-continuation task (McPherson et al 2018). In 612 that study, synchronization-continuation accuracy was negatively correalted with the overall 613 isochrony of spontaenous tapping, however not to participants' personal SMT rate.…”
Section: Preferred Motor and Perceptual Rhythms 533supporting
confidence: 86%
“…The notion of a personal tempo has been around for decades (Rimoldi 566 1951), but although some studies look at within-subject consistency across trials, this is often 567 limited to a small number of trials/sessions (Schwartze and Kotz 2015) and individual 568 differences in test-retest reliability are rarely reported. Indeed, similar to the current findings, 569 a recent study showed that individuals vary substantially in the degree of isochrony during 570 spontaneous tapping, although in that study SMT replicability across trials/session was not 571 tested (McPherson et al 2018). Test-retest replicability of PPT is even less prevalent, and as 572 mentioned above, measurement of the PPT itself is often skewed toward the SMT by 573 experimental design.…”
Section: Preferred Motor and Perceptual Rhythms 533supporting
confidence: 72%
See 1 more Smart Citation
“…Value of the Data These data constitute a failure to replicate previous reports of a correspondence between motor and perceptual “most comfortable” rhythms [2] , [3] , [4] , [5] , [6] , [7] , [8] . They reveal substantial variability in spontaneous rhythmic behavior – both within and across modalities - which is often overlooked when reporting only summary metrics (means).…”
mentioning
confidence: 92%
“…It is often performed as a finger tapping task in synchrony with an external rhythm, usually a steady metronome beat (Repp and Su, 2013). Along with the synchronization paradigm, synchronization-continuation tasks are often used to assess entrainment to an external rhythm (Flach, 2005;Ullén et al, 2008;Avanzino et al, 2013;McPherson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%